Nonlinear Volterra delay evolution inclusions subjected to nonlocal initial conditions - Yu, Yang-Yang; Wang, Rong-Nian; Vrabie, Ioan I. (Topological Methods in Nonlinear Analysis, 2021)
This paper deals with a nonlinear Volterra delay evolution inclusion subjected to a nonlocal implicit initial condition. The evolution inclusion involves an $m$-dissipative operator (possibly multivalued and/or nonlinear) and a noncompact interval. We first consider the evolution inclusion subjected to a local initial condition and prove an existence result for bounded $C^0$-solutions. Then, using a fixed point theorem for upper semicontinuous multifunctions with contractible values, we obtain a global solvability result for the original problem. Finally, we present an example to illustrate the abstract result.